Evaluation of In vitro Antioxidant and In vivo Pharmacological Activity of Leaf Extracts of Hoya parasitica (Wall.) - Ummee Habiba Tania, Md Rajib Hassan, Nusrat Jahan Eshita, Rumana Akhter, Mohammad Shahriar (Journal of Applied Pharmaceutical Science, 2016)
In present study, leaf extract of Hoya parasitica Wall. was evaluated for in vitro antioxidant and membrane stabilizing activity along with in vivo gastro intestinal motility and acute toxicity. Five different assays were performed to evaluate antioxidant activity. In DPPH free radical scavenging activity, methanol, ethanol and chloroform extract exhibited IC50 value similar to standard ascorbic acid. The presence of flavonoid and phenolic contents was also similar in all the plant extracts. However, chloroform extract showed remarkable reducing power capacity (69.10% at 200µg/mL). In case of membrane stabilization, the chloroform extract showed maximum inhibition (32.62 %) of haemolysis, whereas the ethanol extract showed a significant (p
Keywords: Hoya parasitica, Membrane stabilizing, In vitro antioxidant activity, IC50, toxicity, GI motility.